Numerical simulation of hot press forming process for quenchable sheet metal between nanocoolant and chilled water - S. K., Lim; M. F., Zamri; A. R., Yusoff (2018)
This paper presents the numerical simulation of hot press forming process by introducing nanocoolant compared with chilled water into the cooling channel system of HPF tool. By using thermal analysis, the heat distribution between heated blank and tools are evaluated. The thermal analysis results show that the average enhancement of nanocoolant cooling rate is measured to be 30.2% higher compared with chilled water. The simulation data are validated with experimental hot press forming results. This study recommends nanocoolant for application in cooling channel system of hot press forming process.